1997
DOI: 10.4319/lo.1997.42.4.0663
|View full text |Cite
|
Sign up to set email alerts
|

Internal seiche climatology in a small lake where transversal and second vertical modes are usually observed

Abstract: From the analysis of thermistor chain data recorded in a small clongatcd lake, compared with the results of numerical simulations, second vertical modes of the internal scichcs are shown to be active during more than twothirds of the whole stratifcd period, although no rcsonancc with the wind is observed. On the other hand, due to the wind pattern, transversal seiches (mainly the first vertical mode) are also usually excited and they somctimcs dominate. At the end of the stratified period, however, when the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 12 publications
5
40
0
Order By: Relevance
“…So, in general, the horizontal modes in 2013 were higher. The development of nodal lines at locations where the transversal section is relatively small in comparison to the mean transversal area of the lake is well known (Roget et al, 1997;Imam et al, 2013). According to our results, the decrease of 3.2 m in the surface level between 2006 and 2013 seems to have favored the development of a nodal line at a seal near the entrance to Chernyshev Bay, where the depth was less than 5 m in 2013.…”
Section: Horizontal Structure Of the Internal Seichesmentioning
confidence: 58%
See 1 more Smart Citation
“…So, in general, the horizontal modes in 2013 were higher. The development of nodal lines at locations where the transversal section is relatively small in comparison to the mean transversal area of the lake is well known (Roget et al, 1997;Imam et al, 2013). According to our results, the decrease of 3.2 m in the surface level between 2006 and 2013 seems to have favored the development of a nodal line at a seal near the entrance to Chernyshev Bay, where the depth was less than 5 m in 2013.…”
Section: Horizontal Structure Of the Internal Seichesmentioning
confidence: 58%
“…In 2006, however, the longitudinal mode of 11 h also had a transversal structure at the southern part of the lake and in 2013 the longitudinal mode of 7 h had a crosswise nodal line encompassing 0.4 • of latitude. The importance of the wind pattern in determining the standing waves that become excited from the spectrum of possibilities has been illustrated by different authors (Valerio et al, 2012) and the excitement of longitudinal seiches with a transversal structure at the wider and deeper lobe has also been documented in a small lake as the standard response to an oblique or transversal wind forcing (Roget et al, 1997).…”
Section: Horizontal Structure Of the Internal Seichesmentioning
confidence: 99%
“…The PK69 model has been widely accepted within the oceanographic community (Gregg 1999), which also uses the very similar Nasmyth (1970, hereafter N70) model obtained experimentally. Regarding microstructure temperature, the spectral model proposed by Batchelor (1959, hereafter B59) is widely accepted and extensively used in oceanic and limnic waters to obtain « (Wü est et al 1996;Saggio and Imberger 2001), but lately proposals have been made (Nash and Moum 2002;Roget et al 2006;Sanchez and Roget 2007) to consider the alternative model given by Kraichnan (1968, hereafter K68).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of high-vertical mode internal waves are seldom reported because these modes have been traditionally deemed rare in nature (e.g., Stevens and Lawrence 1997). Second vertical modes, for example, have been reported by LaZerte (1980), Wiegan and Chamberlain (1987), and Roget et al (1997), among others. Mü nnich et al (1992) showed that the second vertical mode V2H1 is dominant in the internal wave field of Alpnacher See, a side basin of Lake Lucerne.…”
mentioning
confidence: 99%